2020
DOI: 10.3390/su12239804
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation and Stress as Predictors of Productivity Perception and Remote Work Satisfaction during the COVID-19 Pandemic: The Role of Concern about the Virus in a Moderated Double Mediation

Abstract: From mid-March to the end of May 2020, millions of Italians were forced to work from home because of the lockdown provisions imposed by the Italian government to contain the COVID-19 epidemic. As a result, many employees had to suddenly switch to remote work, experiencing both troubles and opportunities. Social isolation from colleagues and the workplace represents a typical aspect of remote work which increased significantly during the social confinement imposed by the government. This study investigates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
256
5
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(284 citation statements)
references
References 41 publications
19
256
5
4
Order By: Relevance
“…Many employees and students resorted to abrupt transitions towards remote work and social distancing due to public health measures. Subsequent social isolation has directly influenced workers' perceptions of productivity and remote work satisfaction [13]. These findings further support a synthesis of PsyCap interventions and their relation to productivity.…”
Section: Introductionsupporting
confidence: 63%
“…Many employees and students resorted to abrupt transitions towards remote work and social distancing due to public health measures. Subsequent social isolation has directly influenced workers' perceptions of productivity and remote work satisfaction [13]. These findings further support a synthesis of PsyCap interventions and their relation to productivity.…”
Section: Introductionsupporting
confidence: 63%
“…Research on remote work indicates that temporarily performing duties away from the workplace can increase employee job satisfaction [ 40 ]. In contrast, research conducted under social isolation and COVID stress suggested that isolation negatively affects remote job satisfaction [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…In pre-pandemic remote work, social support was a strong predictor of work success and satisfaction. (Toscano & Zappalà, 2020;Wang et al, 2020). Social support was even more critical during COVID-19 due to the social isolation experienced while physical distancing.…”
Section: Discussionmentioning
confidence: 99%